Analisis frekuensi, durasi, dan intensitas suara laki-laki dan perempuan bahasa Banjar menggunakan perangkat lunak Praat - Ningrum, Dwi Kurnia Surya; Suriyani, Siti; Syarfina, Tengku (Universitas Lampung, 2024)
This study aims to identify and analyze differences in the frequency, duration, and intensity of sound between male and female speakers of the Banjarnese. The research method is an experimental approach that utilizes a mixed method combining qualitative and quantitative analyses. Additionally, the study utilizes an instrumental approach, where the researcher employs the Praat program to analyze the frequency, intensity, and duration of sound produced by male and female speakers of the Banjarnese. Data were collected from one male and one female speaker of the Banjarnese. The analysis indicates that the frequency of sound produced by male speaker of the Banjarnese tends to be lower than that of female speaker. The duration of sound produced by male speaker is also shorter compared to that of female speaker. Furthermore, the intensity of sound produced by male speaker tends to be lower than that of female speaker. This study confirms the presence of significant differences in vocal characteristics between male and female speakers of the Banjarnese. These results suggest the existence of distinct linguistic patterns among genders within the Banjarnese community.Keywords: Banjarnese, Durations, Frequencies, Intensities, Praat Application